UPAYA MENINGKATKAN HASIL BELAJAR PASSING BAWAH BOLA VOLI MENGGUNAKAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) PADA SISWA KELAS XI - Latief Alfadzoli, Muhammad; Darumoyo, Kuncoro; Bayu Utomo, Andy Widhiya (Dharmas Journal of Sport, 2024)
This research aims to determine the effect of the Team Games Tournament (TGT) learning model on volleyball bottom passing learning outcomes. Underpassing is one of the techniques in the game of volleyball, underpassing and overpassing techniques are used to provide feedback to a friend to carry out an attack or in other words move the ball to a teammate to continue as an attack on the opponent. Based on observations made at Al-Islam Ngawi Vocational School, there were problems experienced by students in the Physical Education learning process. Practical results are still low, namely the minimum completeness criteria (KKM) of 75 have not been met. Like in class XI, which has 10 students, many of them have not met the KKM. Among the students who got a score >75 were 2 children, and those who got a score <75 were 8 children. This means that 80% of those who have not met the minimum completion criteria (KKM) in class XI are 80% and only 20% have passed. With the Team Games Tournament (TGT) learning model, it can improve student learning outcomes from psychomotor, affective and cognitive aspects, and can improve the quality of learning. From this research, it was stated that there was an increase in learning outcomes for volleyball underpassing by 13.63% from cycle I to cycle II and that learning outcomes (meeting the KKM) could be successfully achieved with a minimum completion requirement of 80% of the number of students.